Answer:
Explanation:
F(x) = x² - 2x + 1
= (x - 1)²
By comparing this equation with the vertex form of the quadratic equation,
y = (x - h)² + k
Here, (h, k) is the vertex
Vertex of the parabola → (1, 0)
x-intercepts → (x - 1)² = 0
x = 1
y-intercepts → y = (0 - 1)²
y = 1
Now we can draw the graph of the given function,
From this graph,
As x → 0,
![\lim_(x \to 0^(-)) (x-1)^2=1](https://img.qammunity.org/2022/formulas/mathematics/high-school/idhjiv473sizooopquf68sioosxunva01z.png)
![\lim_(x \to 0^(+)) (x-1)^2=1](https://img.qammunity.org/2022/formulas/mathematics/high-school/b86xqgrftlywkmwvigbm11e3zs0uoxcg8l.png)
f(0) = (0 - 1)²
= 1
Since,
![\lim_(x \to 0^(-)) (x-1)^2=\lim_(x \to 0^(+)) (x-1)^2=1](https://img.qammunity.org/2022/formulas/mathematics/high-school/gzes41b2dt8vmgsf1m87ox560qppasa6y9.png)
Therefore, given function is continuous at x = 0.